2008
DOI: 10.1007/s10459-008-9098-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based medical education is no better than problem-based discussions and induces misjudgment in self-assessment

Abstract: Simulation-based teaching (SBT) is increasingly used in medical education. As an alternative to other teaching methods there is a lack of evidence concerning its efficacy. The aim of this study was to evaluate the potency of SBT in anesthesia in comparison to problem-based discussion (PBD) with students in a randomized controlled setting. Thirty-three fourth-year medical students attending a curricular anesthesiology course were randomly allocated to either a session of SBT or a session of PBD on an emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…Wenk et al (2008) demonstrated that both problem-based discussion and simulation-based teaching have comparable outcomes in theoretical knowledge and clinical skill. Steadman et al (2006) found simulation base learning to be superior to problem-based learning in the context of critical assessment and management skills acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wenk et al (2008) demonstrated that both problem-based discussion and simulation-based teaching have comparable outcomes in theoretical knowledge and clinical skill. Steadman et al (2006) found simulation base learning to be superior to problem-based learning in the context of critical assessment and management skills acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used a randomized controlled trial design to compare simulationbased learning with problem-based discussion but their findings were controversial (Steadman et al 2006;Wenk et al 2008). Wenk et al (2008) demonstrated that both problem-based discussion and simulation-based teaching have comparable outcomes in theoretical knowledge and clinical skill.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a simulation exercise using a blood pressure arm task trainer can improve students' blood pressure measuring technique but does little to develop their communication or assessment skills. 19,20 A significant disadvantage of the use of simulation in health professionals' education is the cost of sophisticated equipment. An individual high-fidelity simulator costs on average $30,000.…”
Section: Disadvantages Of Simulation In Health Care Educationmentioning
confidence: 99%
“…An institution will also need space to conduct the simulation and house the equipment. 3,14,20 Although one of the key advantages of simulation is the ability to provide immediate feedback to students, to do so requires adequate faculty resources to conduct the simulation and assess the students. Not only do faculty members need to be trained in conducting the simulation but they also must have the clinical knowledge to teach and assess students.…”
Section: Disadvantages Of Simulation In Health Care Educationmentioning
confidence: 99%
“…Borges et al 55 did not observe significant changes in practicing anesthesiologists' airway management of a ''cannot intubate, cannot ventilate'' simulated scenario following simulation training. Wenk et al 56 compared simulation-based learning with problem-based learning on anesthesia students' ability to perform a rapid sequence intubation on a full-body mannequin. Following the training session, students in both groups performed equally well on the rapid sequence intubation task.…”
Section: Changes In Learner Perceptionsmentioning
confidence: 99%